SO2 influence on the K/La2O3 soot combustion catalyst deactivation - Peralta, María Ariela (2008)
In the present work, K/La2O3 was prepared and tested as a potential catalyst to be used in a diesel engine exhaust. The soot combustion activity was evaluated by TPO, and the NOx - catalyst interaction was studied using a microbalance experiment. The SO2 poisoning process and the regeneration of a poisoned K/La2O3 catalyst were analyzed. The fresh catalyst presented a good soot combustion activity. After being treated with a 1000 ppm SO2 stream, the catalyst was poisoned due to lanthanum sulfate and potassium sulfate formation.  The NOx treatment contributed to the K2(SO4) decomposition at the expense of extra La2(SO4)3 formation and the H2 treatment contributed to the La2(SO4)3 decomposition